Redescription of Tripleurospermum heterolepis (Asteraceae), endemic to Turkey - Inceer, Huseyin (Phytotaxa, 2015)
Tripleurospermum heterolepis (Freyn & Sintenis) Bornmüller has been poorly known as a local endemic species classified within DD category of IUCN. It had not been collected since its introduction to scientific community in 1895. In 2007, T. heterolepis was rediscovered in its type locality. Based on its syntypes deposited at B and G as well as the new specimens collected from the type locality, a misdescription of the species in the Flora of Turkey and the East Aegean Islands is also reported. A new description of T. heterolepis, amended and extended, is presented here, and its updated conservation status is indicated. The diagnostic morphological characters that distinguish the species from its close relatives are discussed.